Proteolysis of the class II-associated invariant chain generates a peptide binding site in intracellular HLA-DR molecules. - Roche, P A (1991)
HLA-DR molecules are heterodimeric transmembrane glycoproteins that associate intracellularly with a polypeptide known as the invariant (I) chain. Shortly before expression of the HLA-DR alpha beta dimer on the cell surface, however, the I chain is removed from the intracellular alpha beta I complex by a mechanism thought to involve proteolysis. In this report, we show that treatment of purified alpha beta I with the cysteine proteinase cathepsin B results in the specific proteolysis of the HLA-DR-associated I chain in vitro. As a consequence of this, the I chain is removed and free alpha beta dimers are released from alpha beta I. Although alpha beta I fails to bind an immunogenic peptide, the released alpha beta dimers acquire the ability to bind the peptide after proteolysis of the I chain. These results suggest that the I chain inhibits immunogenic peptide binding to alpha beta I early during intracellular transport and demonstrate that proteolysis is likely to be the in vivo mechanism of I chain removal.